A Study on Analysis of Sinter Microstructure and Phase Morphology - Ömer Saltuk Bölükbaşı (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Sinter is a blast furnace input material obtained by heating to 900-1200 oC without full melting and adhering to each other with superficial melting. It is considered as a multi-phase material with its sinter heterogeneous microstructure. In general, the main mineral phases are hematite, magnetite, silicoferrite of calcium and aluminium (SFCA) and silicates. By determining the SFCA structure in the sinter material, the sintering process will be made more stable and important parameters affecting the quality in the sintering process will be examined. Sinter material obtained from iron ore, iron and steel industry by products and auxiliary materials. The scope of this project is the determination of the amount of SFCA formed by bonding SiO2, CaO, Fe2O3, Al2O3 and MgO compounds and monitoring this value as a parameter by the enterprise. Sinter samples having different characteristic features will be made ready for X-ray diffraction (XRD) and optical microscopy inspections by polishing, etching and freezing in epoxy for mineralogical researches. Before raw data obtained from the analysis is evaluated at Autoquan, they will be converted into Autoquan format and then, they will be read in XRD device and mineralogical composition of the sinter will be revealed by XRD analyses. Detailed view of mineralogical compounds will be investigated so as to complete scanning electron microscope (SEM) analyses and XRD analyses; elemental composition of the compounds and valence conditions of the elements will be researched by energy dispersive spectroscopy (EDS) method. Hematite, magnetite, calcium ferrite phase structures in different formations will be studied subject to melting and temperature during optical microscopy studies conducted on sinter samples. Furthermore, it will be researched variations of SFCA, SFCA-I and SFCA-II phase structures within the sinter matrix subject to different raw material input and process parameters. It will be ensured to interpret the results through rietveld method.